INTERDISCIPLINARIDADE E PRODUTIVISMO NOS PROGRAMAS DE PÓS-GRADUAÇÃO STRICTO SENSU DA ÁREA DE NUTRIÇÃO DA CAPES NO BRASIL DE 1998 A 2013 - Myriam de Lima Ramagem Martins (Universidade do Estado do Rio de Janeiro, 2014)
The study deals with social relations associated to the scientific field of Food and Nutrition (F&N) andtakes as its empirical reference to its development, the postgraduate programs included in the area called" Nutrition " under Coordination of Higher Education Improvement Personnel (CAPES) . We discussabout the functions of elements, positions, arguments, interests and rules which are introduced in thegame of researchers' formation and the production and acquisition of knowledge that occurs in the field ofF & N, starting from the concept of scientific field by Pierre Bourdieu. We consider that the field of F & Nis recent constituted, interdisciplinary and in a very intense activity process in order to build its scientificautonomy. This space is very susceptible to the influences of CAPES regarding to the criteria for assessmentsof postgraduate programs. Productivism - in its identity with the market's economy and competition betweenagents and their deleterious consequences on health - seems to present itself as a problem in this scientificfield. The interdisciplinarity which identifies this science field, involves assessment procedures that includesuch epistemic plurality, given to the remarkable biomedical hegemony in the assessment criteria of thepostgraduate field of F & N and health area. Rating is a difficult construction process, which is essentialto assume the existence of different cultures between the sciences, besides the importance and necessityof mutual support between the agents so that the diversities are embraced and men are valued as human. DOI: http://dx.doi.org/10.12957/demetra.2014.13256